Linear voting rules - Hans Peter Grüner; Thomas Tröger (University of Mannheim, Department of Economics, 2018)
How should a society choose between two social alternatives if participation in the decision process is voluntary and costly and monetary transfers are not feasible? Considering symmetric voters with private valuations, we show that it is utilitarian-optimal to use a linear voting rule: votes get alternativedependent weights, and a default obtains if the weighted sum of votes stays below some threshold. Standard quorum rules are not optimal. We develop a perturbation method to characterize equilibria in the case of small participation costs and show that leaving participation voluntary increases welfare for linear rules that are optimal under compulsory participation.
urn:nbn:de:bsz:180-madoc-436284
Keywords: D71; D72; D82; 330; Mechanisms design; optimal voting rules; costly voting; compulsory voting; quorum rules